The effect of baseline pressure errors on an intracranial pressure-derived index: results of a prospective observational study - Eide, Per Kristian (BioMed Central, 2014)
BACKGROUND: In order to characterize the intracranial pressure-volume reserve capacity, the correlation coefficient (R) between the ICP wave amplitude (A) and the mean ICP level (P), the RAP index, has been used to improve the diagnostic value of ICP monitoring. Baseline pressure errors (BPEs), caused by spontaneous shifts or drifts in baseline pressure, cause erroneous readings of mean ICP. Consequently, BPEs could also affect ICP indices such as the RAP where in the mean ICP is incorporated. METHODS: A prospective, observational study was carried out on patients with aneurysmal subarachnoid hemorrhage (aSAH) undergoing ICP monitoring as part of their surveillance. Via the same burr hole in the scull, two separate ICP sensors were placed close to each other. For each consecutive 6-sec time window, the dynamic mean ICP wave amplitude (MWA; measure of the amplitude of the single pressure waves) and the static mean ICP, were computed. The RAP index was computed as the Pearson correlation coefficient between the MWA and the mean ICP for 40 6-sec time windows, i.e. every subsequent 4-min period (method 1). We compared this approach with a method of calculating RAP using a 4-min moving window updated every 6 seconds (method 2). RESULTS: The study included 16 aSAH patients. We compared 43,653 4-min RAP observations of signals 1 and 2 (method 1), and 1,727,000 6-sec RAP observations (method 2). The two methods of calculating RAP produced similar results. Differences in RAP ≥0.4 in at least 7% of observations were seen in 5/16 (31%) patients. Moreover, the combination of a RAP of ≥0.6 in one signal and <0.6 in the other was seen in ≥13% of RAP-observations in 4/16 (25%) patients, and in ≥8% in another 4/16 (25%) patients. The frequency of differences in RAP >0.2 was significantly associated with the frequency of BPEs (5 mmHg ≤ BPE <10 mmHg). CONCLUSIONS: Simultaneous monitoring from two separate, close-by ICP sensors reveals significant differences in RAP that correspond to the occurrence of BPEs. As differences in RAP are of magnitudes that may alter patient management, we do not advocate the use of RAP in the management of neurosurgical patients.